2022
DOI: 10.1055/s-0041-1742240
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of the Delayed–Immediate Microsurgical Breast Reconstruction: Extending the Choice

Abstract: Background Deep inferior epigastric perforator (DIEP) reconstruction can be performed in an immediate (at time of mastectomy), delayed–immediate (immediate tissue expander followed by staged DIEP), or delayed timing following mastectomy. Avoiding flap radiation is a known benefit of the delayed–immediate approach. The purpose of this study is to evaluate patients who chose DIEP flap as the reconstructive method during initial consultation and compared characteristics of surgery in relation to their final recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…There have been several reports of increased fat necrosis in reconstructed breasts treated with radiotherapy [14][15][16][17][18] In this regard, immediate-delayed reconstruction has been recommeded as an option to avoid radiation therapy to the autologous reconstruction. [19][20][21] Alternatively, our study found that the volume ratio of the reconstructed breast had no decrease in the radiotherapy group, which was in accordance with other previous reports (p = 0.222, Supplementary Table 1). 22,23 This result may be due to the lower incidence of fat necrosis in our study population.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…There have been several reports of increased fat necrosis in reconstructed breasts treated with radiotherapy [14][15][16][17][18] In this regard, immediate-delayed reconstruction has been recommeded as an option to avoid radiation therapy to the autologous reconstruction. [19][20][21] Alternatively, our study found that the volume ratio of the reconstructed breast had no decrease in the radiotherapy group, which was in accordance with other previous reports (p = 0.222, Supplementary Table 1). 22,23 This result may be due to the lower incidence of fat necrosis in our study population.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…7 8 The reasons for this include (1) early reports of higher flap complication rates in immediate reconstruction followed by radiation, (2) limitations in treatment planning due to guidelines for postmastectomy radiation based on findings discovered at the time of mastectomy, and (3) potential for the flap to interfere with effective delivery of radiation to the chest wall. 9 10 11 12 22 23 24 25 26 The optimal timing of reconstruction after radiation remains an ongoing debate. Many believe that longer delays allow for recovery of acute inflammatory changes induced by radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although patient and treatment factors guide discussions and decisions for timing of reconstruction with anticipated radiation therapy (RT), delayed or delayed-immediate reconstruction remains the most common approach with anticipated radiation. 7 8 9 10 11 12 The prevailing assumption is that longer delays are needed to allow sufficient time for recovery of radiation treatment effects to tissues. This is supported by studies reporting higher complications rates when reconstruction is performed before 12 months.…”
mentioning
confidence: 99%
“…29 30 31 There may also be cost savings related to choosing delayed-immediate as opposed to immediate DIEP flap reconstruction, as this option has been associated with shorter operative time, and this finding should be explored in future work. 32…”
Section: Discussionmentioning
confidence: 99%